Dysphagia in amyotrophic lateral sclerosis: prevalence and clinical findings. (14th May 2013) - Ruoppolo, G.; Schettino, I.; Frasca, V.; Giacomelli, E.; Prosperini, L.; Cambieri, C.; Roma, R.; Greco, A.; Mancini, P.; De Vincentiis, M.; Silani, V.; Inghilleri, M.
Abstract : Objectives: To characterize swallowing deficits in amyotrophic lateral sclerosis (ALS); investigate the delay in dysphagia onset; estimate correlations between dysphagia severity and patients' functional status; identify the symptom(s) most likely to predict dysphagia. Materials and methods: A group of 49 consecutive patients with ALS, 14 with bulbar onset and 35 with spinal onset, underwent swallowing evaluation including bedside and fiberoptic endoscopic examination to detect dysphagia. Results: Patients with dysphagia were more likely than those without to have bulbar onset ALS ( P = 0.02); more severely impaired chewing ( P = 0.01); and tongue muscle deficits ( P = 0.001). The only variable measured at first examination significantly associated with dysphagia was a more than mild tongue muscle deficit. The only variable useful in predicting dysphagia was a chewing deficit. In 10 of the 49 patients studied, swallowing evaluation disclosed an impaired cough reflex. Conclusions: Dysphagia in patients with ALS correlates significantly with bulbar onset and with oral swallowing impairment. Fiberoptic swallowing evaluation is a useful tool for detecting swallowing deficits and laryngeal sensitivity in patients with ALS. An impaired cough reflex is an unexpected finding in many patients with ALS.